Meddling friends and family: Dark Tetrad traits predict interference in disliked couples' romantic relationships. (July 2021) - Collisson, Brian; Howell, Jennifer L.; Monleon, Jasmine
Certain disapproving friends and family may interfere in others' romantic relationships by undermining commitment processes. In the current study, we assessed whether friends and family members' scores on the Dark Tetrad, a constellation of socially aversive personality traits including narcissism, Machiavellianism, psychopathy, and sadism, predict relationship interference. In Study 1, 206 people selected a friend who was currently in a romantic relationship they disliked or disapproved of. They then indicated how often they interfered in the disliked couple's relationship, completed measures of the Dark Tetrad, and additional measures of interest (e.g., gender, closeness to the target of interference). In Study 2, 180 people selected a family member who was currently or formerly in a disliked relationship, before completing the same measures. In both studies, overall dark personality and closeness to the friend or family member positively correlated with relationship interference. Additionally, when controlling for overall dark personality and the other Dark Tetrad traits, sadism specifically predicted interference with friends' relationships; high narcissism and, surprisingly, low Machiavellianism predicted interference with family members' relationships. Implications for dark personality traits and relationships are discussed.